Persistence of government funding in small business finance - Ilkka Ylhäinen (The Research Institute of the Finnish Economy (ETLA), 2010)
This paper studies the interaction of Finnish manufacturing firms and a state-owned specialized financing company, whose objective is to cure credit market imperfections. The study ex-amines how the presence of such agency affects the behavior of the firms over time. Specifically, the study analyzes whether the observed persistence in the subsidized financing originates from true state dependence or unobserved firm-specific heterogeneity. The results show that there is positive state dependence in the granted government loans and guarantees. The findings indicate that the private sector agents may adjust their financing behavior in response to the government intervention in the credit markets. The unobserved firm-specific heterogeneity accounts for much of the observed persistence, which provides another reason for why some firms are more dependent on the government funding than the others.
Keywords: G21; G24; G32; H81; 330; credit market imperfections; small business finance; government funding